Improving Man Power Productivity Using Work Load Analysis in PT. Abadi Surya - Rendy Rendy (President University, 2016)
ABSTRACT The research is accomplished by measuring the workload of officers of HCGS Division in PT HGS. This measurement will be used for determining the man power required by each position. Based on initial observation, there is imbalance workload distribution among the employees leads to the low employee productivity. Therefore, the workload analysis is needed to find the appropriate workload allocation among employees. The productivity is analyzed by measuring work load and Full Time Equivalent (FTE) standardization using 17 positions of HCGS Division and the expert officer as sample. The employee FTE is compared to the company’s FTE and gap analysis is done. Gap will be classified using FTE Index. Next, the unbalance workload will be minimized by determining the man power of each position. Several alternatives of man power planning are provided by analyzing the advantages and disadvantages of each alternative. The result of this study is to provide the best strategy for reducing the unbalance of workload.